Effects of multi-disciplinary team nursing model combined with high-fiber dietary intervention on blood glucose level and nutritional status in elderly type 2 diabetes patients: a prospective clinical trial - Wang, Haiyun; Yan, Mengping; Wang, Hongyin; He, Lingbo; Zhang, Yingzi (Frontiers in Medicine, 2025)
ObjectiveThis study was a prospective clinical trial, aimed to explore the effects of multi-disciplinary team (MDT) nursing model combined with high-fiber dietary intervention on blood glucose level and nutritional status in elderly diabetes patients.MethodsOne hundred and sixty-eight elderly type 2 diabetes patients admitted from April 2020 to April 2023 were allocated into intervention group and control group. Patients in the control group accepted routine nursing + basic nutritional therapy. On the basis of the control group, patients in the intervention group adopted MDT nursing + high-fiber dietary intervention. Both groups received an 8-week intervention. The blood glucose indexes, incidence of complications, quality of life, nutritional status, negative emotions, sleep quality along with patient satisfaction were compared in two groups.ResultsAfter 8 weeks of intervention, when comparing with the control group, the fasting blood glucose, 2 h postprandial blood glucose as well as glycosylated hemoglobin in the intervention group were lower (p < 0.05), the incidence of complications in the intervention group was lower (p < 0.05), the scores of body function, psychological state, social function along with role function in the intervention group were higher (p < 0.01), the ALB and TP levels in the intervention group were higher (p < 0.05), the SAS and SAS scores in the intervention group were lower (p < 0.05), the PSQI score in the intervention group were lower (p < 0.05), and the patient satisfaction in the intervention group was higher (p < 0.05).ConclusionMDT model in combination with high-fiber dietary intervention can control blood glucose level, promote nutritional status, decrease the incidence of complications along with promote the quality of life in elderly diabetes patients.